Hubungan Nilai Aliran Puncak Ekspirasi (APE) dengan Kualitas Tidur pada Pasien PPOK di Poli Spesialis Paru B Rumah Sakit Paru Jember (Correlation between Peak Expiratory Flow Rate (PEFR) and Sleep Quality of Patient with COPD at B Lung Specialist Unit of - Riska Umi Yatun; Nur Widayati; Retno Purwandari (Pustaka Kesehatan, 2016)
Chronic obstructive pulmonary disease (COPD) is a lung disease characterized by obstruction to airflow that is persistent and progressive. Shortness of breath and low PEFR is major problem in COPD. Shortness of breath during sleep can increase reticular activating system and release norepinephrine which cause waking state and sleep disorder. The purpose of this study was to analyze the correlation between PEFR and sleep quality in COPD patients.The study design was correlation analytic with cross-sectional approach involving 53 patients as a sample. Data were collected by using peak flow meter to measure PEFR and PSQI questionnaire to measure quality of sleep. Data were analyzed by using Spearman rank test with significance level of 0.05. The result showed that the average value of PEFR was 41.09% and more than half of respondents (71.7%) had PEFR value in red zone category. Mean value of sleep quality was 18.62 and all of respondents had sleep quality in poor category. The p value was 0.000 (p <α) with r value = -0,876. It indicates that there was significant correlation between PEFR and sleep quality in COPD patients. Nurses should provide appropriate intervention to improve PEFR so that COPD patients can have better sleep quality.   Keywords: PEFR, sleep quality, COPD